Body writing : the somatization of truth on the human corporeal form - Tan, Poh Hoon (2014)
Claudine Raynaud, in “Beloved or the Shifting Shapes of Memory”, asserts that the bodily trauma in Beloved “becomes a metaphor for another kind of writing, body writing ” (qtd in Tally 51). My dissertation seeks to examine the act of body writing through scarred, mutilated, and diseased bodies resulting from caste conflict, slavery, and linguistic dissolution. It will focus on the alternative knowledge revealed in human corporeality, where somatic knowledge from material bodies allows for renewal and retelling even in their dislocation. It explores the ways of engraving stories on the body as a result of the anxiety shown towards hegemonic culture, which is revealed in the skepticism towards the adequacy of language in constructing identity and capturing experience.